2021
DOI: 10.1155/2021/5525306
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics Fermentation Technology, a Novel Kefir Product, Ameliorates Cognitive Impairment in Streptozotocin‐Induced Sporadic Alzheimer’s Disease in Mice

Abstract: Alzheimer’s disease (AD) is a neurodegenerative disease characterized by cognitive impairment. Gut microbiota dysfunction (dysbiosis) is implicated in the pathology of AD and is associated with several detrimental consequences, including neurotransmitter depletion, oxidative stress, inflammation, apoptosis, and insulin resistance, which all contribute to the onset of AD. The objective of this study was to assess the effectiveness of Probiotics Fermentation Technology (PFT), a kefir product, in alleviating AD s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 86 publications
(117 reference statements)
1
13
0
Order By: Relevance
“…In summary, the beneficial effects of kefir are associated with its anti-inflammatory and antioxidant properties, as previously demonstrated by us and others [ 40 , 163 , 212 ], preventing apoptosis and, consequently, neuronal degeneration [ 213 , 214 ]. Therefore, this probiotic beverage shows the potential to act as an adjuvant in conventional therapies addressing ND.…”
Section: Targeting the Near Future: Milk Kefir Against Oxidative Stress And Inflammationsupporting
confidence: 57%
“…In summary, the beneficial effects of kefir are associated with its anti-inflammatory and antioxidant properties, as previously demonstrated by us and others [ 40 , 163 , 212 ], preventing apoptosis and, consequently, neuronal degeneration [ 213 , 214 ]. Therefore, this probiotic beverage shows the potential to act as an adjuvant in conventional therapies addressing ND.…”
Section: Targeting the Near Future: Milk Kefir Against Oxidative Stress And Inflammationsupporting
confidence: 57%
“…Aβ [25][26][27][28][29][30][31][32][33][34][35] . Next, we used PC12 cells to further study the indepth mechanism of naringin's neuroprotective effect.…”
Section: Effect Of Naringin On Viability Of Pc12 Cells Injured Bymentioning
confidence: 99%
“…Hyperphosphorylated Tau leads to increased Aβ production; in turn, Aβ accumulation can also increase the activity of GSK-3β [27].…”
Section: Behavioural Neurologymentioning
confidence: 99%
See 1 more Smart Citation
“…Kefir is a dairy product similar to liquid yogurt, is obtained through the fermentation due to the action of a group of yeasts (fungi) and bacteria ( lactobacilli ) [ 75 ]. Recently, the beneficial effects of kefir in AD were assessed: it was demonstrated that kefir ameliorates cognitive impairment in streptozotocin induced mice model of AD [ 76 ]. The latter would be explained, at least in part, by the gut microbiome modulation and enhancement of the insulin/PI3K/Akt pathway, which was demonstrated in another model of sporadic AD [ 77 ].…”
Section: Mechanistic Insights Of Potential Nutraceuticals In Admentioning
confidence: 99%